Simulation of underground coal gasification process in a Bulgarian coal field - Koukouzas, N.; Katsimpardi, I.; Merachev, D. (Bulletin of the Geological Society of Greece, 2013)
The sustainable and environmentally friendly energy production has been a major issue of the world energy sector in recent years. Coal is a major fossil fuel that provides approximately 25% of the total energy demand worldwide; coal reserves still remain significant, although in several cases its exploitation trends to be economically marginal. Underground Coal Gasification (UCG) has been identified as a technology which can bridge the gap between energy production and environmental and financial sustainability. Several UCG trials have taken place, although, there are still questions relative to their safety, performance and applicability. To that direction, modelling can prove to be a very effective and practical tool for the prediction of the project performance and the reduction of the risk involved. UCG is a complex process which incorporates mechanical and chemical processes thus modelling is complex since it demands coupling the aforementioned processes. The current study aims at investigating the applicability of the UCG process in a Bulgarian coal site through 2D modelling. The proposed approach uses FLAC software as a modelling tool and attempts to combine thermal and mechanical effects during the gasification process. Several simulation runs have taken place in an attempt to quantify the effect of the different mechanical and thermal properties of the surrounding rocks to the UCG process, the environmental effects and the stability of the geological formations.